Diagnostic Evaluation of Gastric Motor and Sensory Disorders. (December 2021) - Lacy, Brian E.; Crowell, Michael D.; Cangemi, David J.; Lunsford, Tisha N.; Simren, Magnus; Tack, Jan
Abstract : Abstract: Disorders of gastric motor and sensory function affect 10%-20% of the world's population and adversely impact nutrition, quality of life, work productivity, and health care costs. Classifying these disorders can be challenging given the heterogeneity of symptom presentation, the presence of symptoms unexplained by endoscopic, radiographic and/or laboratory evaluation, and overlap with other luminal gastrointestinal disorders. Accurately diagnosing these highly prevalent disorders relies upon an understanding of epidemiology and risk factors, the ability to take a careful clinical history focused on symptoms, and the presence of predisposing medical, surgical, and psychological conditions. A variety of diagnostic studies are now available to assess gastric motor function and identify maladaptive relaxation, accommodation, and abnormal sensation. FDA-approved treatment options are limited and thus many patients undergo a series of empirical treatment trials that target individual symptoms, often without much benefit. This article provides updated recommendations for identifying and classifying the most common gastric motor and sensory disorders using currently accepted diagnostic tests, and provides a brief supplemental overview on treatment options. "Things sweet to taste prove in digestion sour." –Shakespeare, Richard II, 1595.